¬¬PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS DENGAN MODEL COOPERATIVE LEARNING TIPE CO-OP CO-OP DI SEKOLAH DASAR - Sofia, Ade (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The aim this research to desricribe improved the result of learned studying IPS by Model Cooperative Learning Type Co-op Co-op in class IV SD 09 VII Koto Sungai Sariak. That research use approach qualitative and is quantitative, while this type research that is Research Action Class (PTK) with this device research cover, (1) planning, (2) execution, (3) perception/observation, and (4) reflektion. The result of research becoming result of planning, execution, and result learn student. And can be concluded that study of IPS by using Model Cooperative Learning Type Co-op Co-op can improve result learn the student in class IV SD 09 VII Koto Sungai Sariak. Kata Kunci: hasil belajar, cooperative learning, co-op co-op.